Entrepreneurship in Agriculture: An Innovative Initiative - Ms. Deepa Chauhan, Dr. Deepa Kumari (International Journal of Modern Agriculture, 2020)
Sustainable growth in agriculture sector is an important issue for all the countries. This Paper is an attempt to analyse the significance of agriculture entrepreneurship and government initiatives to strengthen the entrepreneurship spirit. . India had always been an agrarian economy. While from a rote agrarian economy, India is now a witness to growing allied agrarian activities such as food-processing, floriculture, fisheries and many more, there are many basic problems that have been ailing the agrarian ecosystem. The spectrum of problem has only increased with the passage of time that include poor farm output due to a variety of reasons, shrinking land, outdated infrastructure and access to credit for the agrarian community. India has a huge potential to one of the leading agriculture-based economies, if these problems are corrected on time. This paper discusses the role and importance of entrepreneurship in solving the problem of mankind’s oldest profession. This paper takes up cases of three agriprenuerial companies and discusses their forte, intervention and scope for such ventures. The paper also highlights the role of the Indian government in the boosting the necessary steps for agribusiness and its’ growth. Keywords: Entrepreneurship, Start-up, Government, Skill development, economy